Salmonella types found in salmonellosis among children in Ankara - Akman, Muvaffak (The Turkish Journal of Pediatrics, 1961)
The distribution by age group and season of the year of 115 strains of salmonella, isolated in our hospital over a period of three years, is presented. All strains were isolated from blood cultures of Ankara children under 15.